Re-viewing Adult Learning: A Collaborative Self-Directed Learning Model for Adult Educators - Ti'eshia Moore; Joe Houde; Chad Hoggan; Jennie Wagner (Adult Education Research Conference, 2007)
The CSDL model for adult education suggests the incorporation of autonomy and collaboration to traditional SDL. An exploratry model that addresses individual and group choice, control, resources and benefits is proposed.